Identification and analysis of serpin-family genes by homology and synteny across the 12 sequenced Drosophilid genomes. - Garrett, M.; Fullaondo, A.; Troxler, L.; Micklem, G.; Gubb, D. (BMC Genomics, 2009)
The Drosophila melanogaster genome contains 29 serpin genes, 12 as single transcripts and 17 within 6 gene clusters. Many of these serpins have a conserved "hinge" motif characteristic of active proteinase inhibitors. However, a substantial proportion (42%) lacks this motif and represents non-inhibitory serpin-fold proteins of unknown function. Currently, it is not known whether orthologous, inhibitory serpin genes retain the same target proteinase specificity within the Drosophilid lineage, nor whether they give rise to non-inhibitory serpin-fold proteins or other, more diverged, proteins.We collated 188 orthologues to the D. melanogaster serpins from the other 11 Drosophilid genomes and used synteny to find further family members, raising the total to 226, or 71% of the number of orthologues expected assuming complete conservation across all 12 Drosophilid species. In general the sequence constraints on the serpin-fold itself are loose. The critical Reactive Centre Loop (RCL) sequence, including the target proteinase cleavage site, is strongly conserved in inhibitory serpins, although there are 3 exceptional sets of orthologues in which the evolutionary constraints are looser. Conversely, the RCL of non-inhibitory serpin orthologues is less conserved, with 3 exceptions that presumably bind to conserved partner molecules. We derive a consensus hinge motif, for Drosophilid inhibitory serpins, which differs somewhat from that of the vertebrate consensus. Three gene clusters appear to have originated in the melanogaster subgroup, Spn28D, Spn77B and Spn88E, each containing one inhibitory serpin orthologue that is present in all Drosophilids. In addition, the Spn100A transcript appears to represent a novel serpin-derived fold.In general, inhibitory serpins rarely change their range of proteinase targets, except by a duplication/divergence mechanism. Non-inhibitory serpins appear to derive from inhibitory serpins, but not the reverse. The conservation of different family members varied widely across the 12 sequenced Drosophilid genomes. An approach considering synteny as well as homology was important to find the largest set of orthologues.